Ethics in Qualitative Research - Orb, Angelica; Eisenhauer, L.; Wynaden, Dianne (Sigma Theta Tau International. Honor Society of Nursing, Inc., 2001)
Purpose: To critically examine ethical issues in qualitative research.Organizing Construct: The ethical principles of autonomy, beneficence, and justice are guidesfor researchers to address initial and ongoing tensions between the needs and goals of theresearch and the rights of participants.Methods: Research literature, ethics literature, and researcher experiences.Conclusions: Ethical principles can be used to guide the research in addressing the initial andongoing issues arising from qualitative research in order to meet the goals of the research aswell as to maintain the rights of the research participants.